Regime shifts between free-floating plants and phytoplankton: a review - de Tezanos Pinto, Paula (2014)
Field studies evidence shifts between phytoplankton and free-floating plant regimes; yet, it is unclear what drives these shifts and if they are critical transitions (alternative stable states). In this review, we synthesized field and experimental data on free-floating plants (of varying size and phylogenies) and phytoplankton regimes, to assess the effects of these producers on the environment. Nutrient-rich environments promote free-floating plants dominance—regardless of life form—which causes dark and anoxic environments, and nutrient release from sediments. This reinforces free-floating plants dominance, but controls phytoplankton biomass by strong shading (despite high nutrients and low grazing). Phytoplankton dominance renders turbid and oxygen-rich (when producing) environments. We also searched for case studies of regime shifts for free-floating plants and phytoplankton dominance. Most studies showed that when free-floating plants dominance was interrupted, phytoplankton biomass (usually Cyanobacteria) rose steeply. Likewise, when phytoplankton-dominated, the development of dense mats of free-floating plants covers usually controlled phytoplankton. Field evidence that suggests critical transitions include abrupt regime transitions in time and space; yet, evidence including indoor controlled experiments and mathematical models is needed for conclusive evidence of alternative stable states to be drawn.